Study of clinical parameters, diagnostics and outcome in patients with acute respiratory illness in a tertiary care centre during COVID-19 pandemic - Mahavar, Sunil; Tyagi, Princy; Agrawal, Abhishek; Banerjee, Subrata; Sharma, Raman; Keswani, Prakash (International Journal of Advances in Medicine, 2021)
Background: We retrospectively analyzed and compared 98 patients admitted in Intensive care unit (ICU) with symptoms of acute respiratory illness (ARI) during the era of COVID-19 pandemic. Methods: We examined patients presenting in emergency department of SMS Medical College, Jaipur between 3rd and 20th May, 2020 with symptoms of ARI who were tested for SARS-CoV-2. Among those hospitalized, we compared symptoms, vital signs, comorbidities, biochemical and hematological parameters including viral diagnostics. We determined differences in outcomes (ICU admission, interventions, acute respiratory distress syndrome and cardiac injury). Results: In a cohort of 98 patients with symptoms of ARI, 9 (9.183%) tested positive for SARS-CoV-2. Patients were divided into group A and B based on SARS CoV2 RNA testing. Among patients with additional viral testing, no co-infections with SARS-CoV-2 were identified by PCR. FDP and d-dimer was positive in 44.44% patients in group A and 68.53% in group B. 11.11% mortality was observed in group A and 14.606% in group B. The most common complication of ARI observed in both groups was coagulopathy 33.33% in group A and 42.696% in group B. Conclusions: Presence of comorbidities, lymphopenia, elderly age and elevated NLR, TLC, PLR and LDH have been associated with increased morbidity and mortality. Tuberculosis was most common coinfection seen in patients presenting with ARI. ARI due to non-COVID-19 illness was more severe than due to COVID-19 and was accompanied by multiple respiratory and systemic symptoms and was associated with hospitalization.